Iron(III) Triflate and γ-Cyclodextrin-Catalyzed Hydroarylation of Alkenes with 1-Naphthols and 2-Naphthols - Hu, Meng-Xue; Chen, Peng; Miao, Le-Wei; Shi, Jianghuan; Jiang, Yi-Jun (Synlett, 2024)
A Fe(OTf)3 and γ-cyclodextrin-catalyzed hydroarylation of alkenes with 1-naphthols or 2-naphthols is demonstrated. This efficient and general method delivers a wide range of benzylic naphthols from readily available starting materials with high chemo- and regioselectivity in up to 99% yield, with no need for a strong base or additive.
Keywords: naphthols; iron catalysis; cyclodextrin; hydroarylation; alkylation; alkenes